Defect Engineering in Few‐Layer Phosphorene. Issue 16 (23rd March 2018) - Sharma, Ankur; Wen, Bo; Liu, Boqing; Myint, Ye Win; Zhang, Han; Lu, Yuerui
Abstract: Defect engineering in 2D phosphorene samples is becoming an important and powerful technique to alter their properties, enabling new optoelectronic applications, particularly at the infrared wavelength region. Defect engineering in a few‐layer phosphorene sample via introduction of substrate trapping centers is realized. In a three‐layer (3L) phosphorene sample, a strong photoluminescence (PL) emission peak from localized excitons at ≈1430 nm is observed, a much lower energy level than free excitonic emissions. An activation energy of ≈77 meV for the localized excitons is determined in temperature‐dependent PL measurements. The relatively high activation energy supports the strong stability of the localized excitons even at elevated temperature. The quantum efficiency of localized exciton emission in 3L phosphorene is measured to be approximately three times higher than that of free excitons. These results could enable exciting applications in infrared optoelectronics. Abstract : Here, defect engineering in a 3L phosphorene sample via substrate trapping centers is realized. Activation energy of localized excitons in three‐layer phosphorene is measured to be ≈77 meV, indicating relative stability of localized excitons at higher temperatures. The overall quantum efficiency of localized exciton emission in 3L phosphorene is measured to approximately three times higher than that of the free exciton peak.